(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article discusses the integration of innovative methodologies and artificial intelligence (AI) in the educational context, highlighting their contributions to the qualification of teaching practice. Using a qualitative and exploratory approach based on bibliographic research, the study analyzes how resources such as flipped classrooms, gamification, project-based learning, and adaptive platforms, when combined with AI, can promote student leadership and personalized teaching. It is noteworthy that AI, by providing real-time pedagogical data, enhances teaching decision-making and favors more effective interventions. It is concluded that, although promising, this integration requires investment in continuing education, technological infrastructure, and educational policies that ensure the ethical and responsible application of technologies.